2005
DOI: 10.1007/s11273-003-5024-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary production in an impounded baldcypress swamp (Taxodium distichum) at the northern limit of the range

Abstract: The ability of baldcypress (Taxodium distichum) swamps to maintain themselves near the northern limit of their range depends on their levels of production, which is not only a response to climate but also to local environmental factors (e.g., impoundment). We asked if primary production was reduced under impounded conditions and if species' responses to impoundment were individualistic or more generalized. To examine long-term production trends in a permanently impounded baldcypress swamp, a 6-year study of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Results from previous work on the relationship between bald cypress growth and surface‐water depth have been equivocal, with some reporting a negative relationship (Dicke & Toliver, ; Middleton & McKee, ) and some positive (Stahle, VanArsdale, & Cleaveland, ; Young, Keeland, & Sharitz, ). It has been suggested that where wetlands lie above the local water table, increases in surface‐water level may enhance downward delivery of oxygen to the root zone and facilitate growth (Davidson et al, ; Stahle & Cleaveland, ).…”
Section: Resultsmentioning
confidence: 99%
“…Results from previous work on the relationship between bald cypress growth and surface‐water depth have been equivocal, with some reporting a negative relationship (Dicke & Toliver, ; Middleton & McKee, ) and some positive (Stahle, VanArsdale, & Cleaveland, ; Young, Keeland, & Sharitz, ). It has been suggested that where wetlands lie above the local water table, increases in surface‐water level may enhance downward delivery of oxygen to the root zone and facilitate growth (Davidson et al, ; Stahle & Cleaveland, ).…”
Section: Resultsmentioning
confidence: 99%
“…Flooded prairies and marshes (Galatowitsch and van der Valk 1996;Pezeshki et al 2000), riparian and gallery forests (Sweeney et al 2002), mangroves (Feller et al 2003) and swamp forests (Keeland et al 1997;McLeod 2000;Middleton and McKee 2005;Raulings et al 2007) have several examples of such initiatives. In the tropical world, similarly, restoration experience accumulates fast.…”
Section: Introductionmentioning
confidence: 99%
“…According to the serial discontinuity concept, the extent to which a dam alters the river floodplain depends on the position of the dam with respect to the floodplain (Ward and Stanford ). Upstream of dams, wetland tree production declines over time if permanently flooded, so that tree regeneration may be relegated to an elevation‐specific ring in the driest part of the impoundment, e.g., Taxodium distichum forests in Buttonland Swamp, Cache River, Illinois (Middleton and Middleton and McKee , respectively). Freshwater tree species have different tolerances to flooding, so that species compositions may “adjust” to flooding over time depending on flooding depth and seasonality.…”
Section: Repairing Hydrology Of Floodplain Forests and Climate Changementioning
confidence: 99%